An overview of the cycloaddition chemistry of fulvenes and emerging applications - Swan, Ellen; Platts, Kirsten; Blencowe, Anton (Beilstein Journal of Organic Chemistry, 2019)
The unusual electronic properties and unique reactivity of fulvenes have interested researchers for over a century. The propensity to form dipolar structures at relatively low temperatures and to participate as various components in cycloaddition reactions, often highly selectively, makes them ideal for the synthesis of complex polycyclic carbon scaffolds. As a result, fulvene cycloaddition chemistry has been employed extensively for the synthesis of natural products. More recently, fulvene cycloaddition chemistry has also found application to other areas including materials chemistry and dynamic combinatorial chemistry. This highlight article discusses the unusual properties of fulvenes and their varied cycloaddition chemistry, focussing on applications in organic and natural synthesis, dynamic combinatorial chemistry and materials chemistry, including dynamers, hydrogels and charge transfer complexes. Tables providing comprehensive directories of fulvene cycloaddition chemistry are provided, including fulvene intramolecular and intermolecular cycloadditions complete with reactant partners and their resulting cyclic adducts, which provide a useful reference source for synthetic chemists working with fulvenes and complex polycyclic scaffolds.
Keywords: cycloaddition; fulvene; polycyclic scaffolds